Novel renal biomarker evaluation for early detection of acute kidney injury after transcatheter aortic valve implantation. Issue 2 (3rd April 2018) - Arsalan, Mani; Ungchusri, Ethan; Farkas, Robert; Johnson, Melissa; Kim, Rebeca J.; Filardo, Giovanni; Pollock, Benjamin D.; Szerlip, Molly; Mack, Michael J.; Holper, Elizabeth M.
ABSTRACT: Acute kidney injury (AKI) following transcatheter aortic valve implantation (TAVI) is associated with increased morbidity and mortality. The biomarkers neutrophil gelatinase–associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), and interleukin-18 (IL-18) are predictive of AKI after cardiac surgery, but there is little data regarding these biomarkers after TAVI. We evaluated the associations between NGAL, KIM-1, and IL-18 levels and the incidence and severity of AKI and changes in serum creatinine after TAVI. This was a prospective pilot study of 66 TAVI cases. Urinary biomarkers were measured at baseline and at 2, 4, and 12 hours after TAVI. Demographics, procedural features, and renal function until discharge were compared between patients with and without subsequent AKI. Seventeen patients (25.8%) developed AKI postoperatively (stage 1, n = 14; stage 2, n = 1; stage 3, n = 2). There were no significant differences in unadjusted mean NGAL, KIM-1, and IL-18 levels between patients with and without AKI at 2, 4, and 12 hours following surgery. After adjusting for the Society of Thoracic Surgeons risk of mortality, this study of three urinary biomarkers showed no association with AKI or creatinine after TAVI. Ongoing efforts to predict and modify the risk of AKI after TAVI remain challenging.